Critical plane approach to multiaxial variable amplitude fatigue loading - Yingyu Wang; Luca Susmel (Fracture and Structural Integrity)
A new critical plane approach based on the modified Manson-Coffin curve method (MMCCM) is presented in this paper for predicting fatigue lifetime under variable amplitude (VA) multiaxial fatigue loading. The critical plane is assumed to coincide with that material plane experiencing the maximum variance of the resolved shear strain. Fatigue damage is hypothesized to be a function of both the amplitude of the resolved shear strain and the so-called critical plane stress ratio. The latter quantity depends on the mean value and the variance of the stress perpendicular to the critical plane as well as on the variance of the shear stress resolved along the direction experiencing the maximum variance of the resolved shear strain. Load cycles are counted from the resolved shear strain time history by using the classic rain flow counting method. Palmgren-Miner’s linear damage rule is applied to estimate cumulative fatigue damage. The accuracy and reliability of the proposed approach is checked by using several experimental data taken from the literature. The estimated fatigue lives based on the new approach are seen to be in sound agreement with the experimental results.